A Benevolent State Against an Unjust Society? Inequalities in Public Transfers in China. Issue 2 (3rd April 2018) - Shen, Ke; Feng, Wang; Cai, Yong
Abstract: Against the backdrop of a rapid increase in inequality following China's historical economic boom, the Chinese government in the past decade has drastically expanded its social welfare programs aimed in part to reduce inequality. How effective has the benevolent state been and what does it inform us about the nature of the new welfare system in China? Utilizing the National Transfer Accounts approach, we examine inequalities in public transfers in three areas: education, health care, and pension. Public transfers in China as a whole are unevenly distributed across generations, with spending on the elderly almost twice of the young on a per person basis. Public transfers in education, health care, and pension combined are even more tilted, with those in the top income quartile receiving nearly four times of those in the bottom group. Such inequalities are in part conditioned by past legacies of social inequalities in China, but they also show the limits of the emerging Chinese welfare regime.